Understanding Goals of Care for Patients Undergoing Chimeric Antigen Receptor T-Cell Therapy: A Qualitative Descriptive Study - Jones, Danielle (My University, 2024)
Background: Chimeric Antigen Receptor (CAR) T-cell therapy is a relatively novel treatment in Canada for relapsed and refractory leukemias and lymphomas. Limited evidence is available on patient experiences when undergoing this treatment, and there is no research regarding patients’ goals of care (GOC) when undergoing this treatment. Aims: This study aimed to explore patients’ experiences undergoing CAR T-cell therapy, particularly as it related to their GOC. Methods: A qualitative descriptive approach was employed. Information was gathered via semi-structured interviews and medical chart review. Interviews were transcribed and analyzed using content analysis to identify key themes. Results: Six regional patients participated in this study. Ten key themes were identified, highlighting patients’ identified GOC, a lack of implicit GOC discussions, challenging transitions throughout care, and a lack of nursing involvement in GOC discussions. Conclusion: Patients undergoing CAR T-cell therapy have clearly identified GOC (simply to survive) but have not explicitly discussed these goals with their healthcare providers. Overall, patients had positive experiences in receiving care during CAR T-cell therapy but there was opportunities identified to improve care, related to facilitating GOC discussions, increasing support during transitions in care, and optimizing the role of the nurse within GOC conversations. Future research should aim to investigate the experiences of a more varied group of patients including those who were offered and declined receiving CAR T-cell therapy, the perceptions of healthcare providers regarding GOC discussions within CAR T-cell therapy, and the role of nurses in GOC discussions.
Keywords: goals of care; chimeric antigen receptor t-cell therapy; patient experience; hematological malignancy; cancer care; nursing role